"Presenting a Book to Orinda": Anne Twice, Katherine Philips, and John Oldham in New York Public Library, Drexel MS 4175. Issue 4 (4th July 2022) - Arthur, Jake; Ross, Sarah C. E.
ABSTRACT: New York Public Library, Drexel MS 4175 has long been of interest to scholars of early modern music. Titled "Songs vnto the violl and lute" and inscribed "Anne Twice, Her Booke", The manuscript contains a collection of songs for a woman's musical practice and performance in the 1620s. It also, however, contains five poems that have received no attention, including one of outstanding interest: a previously unnoticed poem in praise of Katherine Philips. "Presenting a Book to Orinda" draws liberally on the work of Restoration satirist John Oldham, and likely dates from the early 1680s. The co-presence in the manuscript of Twice's songs and the poem on Philips calls attention to continuities between air singing and poetic exchange as cultural practices engaging women and men across the seventeenth century. This article reconsiders Drexel MS 4175 as a site of lyric collaboration, compilation, and exchange from the 1620s to the 1680s.